Influence of liquor ratio and amount of dyestuff in producing ultradeep black dyeing using mercerised and cationised cotton. (30th March 2016) - Fu, Sha; Farrell, Matthew; Hauser, Peter; Ankeny, Mary
Abstract : Cationised cotton allows the dyeing of cotton fabrics without salt and up to 100% anionic dye utilisation. The employment of cationised cotton in the dyeing of high depths of shades with reactive dyes holds marked potential for sustainable improvements through less dye consumption, decreased water usage, and zero salt utilisation, all while obtaining shade depths darker than possible with conventional reactive dyeings. This work builds upon previous work in obtaining ultradeep dyeings of cotton utilising cationised and mercerised cotton by investigating the effects of liquor ratio in dyeing and amount of dye applied. Surprisingly, for mercerised only cotton fabric, it was found that nearly equivalent depths of shade, as indicated by L *, were obtained, irrespective of the liquor ratio and the amount of CI Reactive Black 5 applied from 7% to 10% owf. However, the strengths of the dyeings, indicated by the K / S sum, show slight increases with increasing amounts of dye, but not when the liquor ratio is lowered. Similarly, for mercerised‐cationised cotton, the liquor ratio had a negligible effect on the depth of shade obtained, but increasing the amount of CI Reactive Black 5 resulted in an increase in shade depth and colour strength. Very deep shades with high colour strength were obtained with mercerised‐cationised cotton that were not obtainable with uncationised cotton, even at a very low liquor ratio and with a drastic increase in the amount of CI Reactive Black 5.